Mining indirect association rules for web recommendation - Kazienko, Przemysław (Zielona Góra: Uniwersytet Zielonogórski)
Classical association rules, here called "direct", reflect relationships existing between items that relatively often co-occur in common transactions. In the web domain, items correspond to pages and transactions to user sessions. The main idea of the new approach presented is to discover indirect associations existing between pages that rarely occur together but there are other, "third" pages, called transitive, with which they appear relatively frequently. Two types of indirect associations rules are described in the paper: partial indirect associations and complete ones. The former respect single transitive pages, while the latter cover all existing transitive pages.
Keywords: association rules; indirect association rules; recommender system; web mining; web usage mining